Experiences of racism of Black medical students and residents in Montréal: “I wear my stethoscope around my neck at all times” (Canadian Medical Education Journal, 2024)
Background: Black students and residents experience racism in medical school. This qualitative study documents Black students’ and residents’ experiences of racism using Critical Race Theory (CRT) and explores their coping mechanisms using the theatrical metaphor.Methods: We conducted semi-structured interviews with four Black medical students and residents (two medical students and two residents) studying in Montréal and analyzed their experiences through counter-stories. We identified themes related to their experiences of racism during medical training and their coping mechanisms.Results: Our analysis reveals these experiences of racism occur in academic and clinical settings (classes, internships, social interactions with peers, faculty, and patients, and through the curriculum), in the form of microaggressions. The analysis also indicates that Black students and residents try to cope with racism using a hyper-ritualization strategy to better fit in (e.g., clothing, behaviours).Conclusion: Considering that Black students and residents experience various forms of racism (subtle or explicit) during their medical training, these findings urge us to increase awareness about racism of students, residents, teachers and health care workers in universities and teaching hospitals. Pathways to increase the representation of Black students and residents seem to be part of the solution, but improving the learning environment must be a priority to improve racial justice in medical training in Québec.